2001
DOI: 10.1098/rspb.2001.1814
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the historical changes in mycorrhizal fungal communities under anthropogenic nitrogen deposition

Abstract: Colours are common stimuli in signalling systems. Requirements to function well as a signal sometimes con£ict between di¡erent signallers, and the same colour stimulus is used to convey completely di¡erent messages to the same receiver. Fruits and aposematic insects both use red coloration as a signal, in the former case to signal pro¢tability and in the latter case as a warning signal. In two experiments, we investigated whether the domestic chick, an omnivorous predator, di¡ered in its unconditioned preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
(42 reference statements)
0
18
0
2
Order By: Relevance
“…Although such studies point to important above-and belowground consequences of biological invasions (Wolfe & Klironomos 2005), too few have been performed to develop general principles about how alien organisms influence soil biodiversity or the underlying mechanisms through which this happens. Second, a growing number of studies have reported responses of belowground community structure to key atmospheric drivers of global change such as elevated CO 2 (Niklaus et al 2003;Yeates et al 2003), temperature ) and nitrogen deposition (Egerton-Warburton et al 2001;Wiemken et al 2001). There are several mechanisms by which these global drivers may affect soil biota, both directly (through affecting the soil organisms themselves) and indirectly (by influencing plant growth characteristics, plant community structure, resource input to the soil) and therefore potentially soil biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although such studies point to important above-and belowground consequences of biological invasions (Wolfe & Klironomos 2005), too few have been performed to develop general principles about how alien organisms influence soil biodiversity or the underlying mechanisms through which this happens. Second, a growing number of studies have reported responses of belowground community structure to key atmospheric drivers of global change such as elevated CO 2 (Niklaus et al 2003;Yeates et al 2003), temperature ) and nitrogen deposition (Egerton-Warburton et al 2001;Wiemken et al 2001). There are several mechanisms by which these global drivers may affect soil biota, both directly (through affecting the soil organisms themselves) and indirectly (by influencing plant growth characteristics, plant community structure, resource input to the soil) and therefore potentially soil biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study for which tree seedlings were inoculated with eight fungal species either singly or in multiple species combinations, several fungal species persisted only in the monoculture treatment, presumably because they were competitively excluded from colonizing seedlings when in combination with fungal species with superior competitive abilities (Jonsson et al 2001). Further, there is evidence that nitrogen fertilization can greatly reduce the diversity on plant roots of both arbuscular mycorrhizal fungi (Egerton-Warburton & Allen 2000;Egerton-Warburton et al 2001) and ectomycorrhizal fungi (Lilleskov et al 2002), probably in part because greater resource availability favours competitive fungal species that suppress subordinate species.…”
Section: B I O T I C D R I V E R S R E S I D E N T I N T H E S O I L mentioning
confidence: 99%
“…Results of a series of greenhouse experiments indicate that N enrichment diminishes the mutualistic functioning of communities of AM fungi at Sevilleta and Shortgrass Steppe (Corkidi et al 2002), at Cedar Creek (Johnson 1993), and at Kellogg (N. C. Johnson, D. L. Rowland, L. Corkidi, and E. B. Allen, unpublished manuscript). Furthermore, in California shrublands, three years of N enrichment resulted in a significant decline in species richness of AM fungi (Egerton-Warburton and Allen 2000, Egerton-Warburton et al 2001) and alterations in mycorrhizal function (Sigü enza 2000). Importantly, AM changes were observed before any shifts in the composition of the aboveground plant community could be perceived.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, work on non-model AM fungal taxa from early-diverging clades (especially the Archaeosporales; Field et al 2016) might provide additional insights, as some traits present at the time, but lost in other taxa, may have persisted in these clades. Historic reconstructions may also be useful to understand the more recent past, such as through the clever use of soil archives to monitor effects of gradual environmental change (Egerton-Warburton et al, 2001), and perhaps resurrection ecology (Franks et al, 2008) can also be explored to learn about the diversity of functional traits of historic AM fungal assemblages and their effects on ecosystem functions. This could open up exciting possibilities to ask questions about any microevolutionary changes that may have occurred, in response to global change drivers or environmental pollutants.…”
Section: Reviewmentioning
confidence: 99%